TINJAUAN YURIDIS TERHADAP KEDUDUKAN SERTIPIKAT HAK MILIK ATAS TANAH BANK PEMERINTAH SETELAH MENJADI PT (PERSERO) (STUDI KASUS PT.BANK SUMUT MEDAN) - REZA FAHMI (PREMISE LAW JURNAL, 2014)
ABSTRACT The changing of legal entity of a certain Bank from a provincial corporation to Corporate has caused the changing in the use of legal provisions on Bank; a provincial corporation which used to be subject to Law No 5/1962 will be subject to Law No. 40/2007 on Corporation after it changes to a Corporate. The research was descriptive analytic and used the theory of legal entity and judicial normative methods. The data were gathered by using secondary data by conducting library research and field study at Bank SUMUT and at the National Land Board Office.The result of the research showed that although the legal entity of Bank SUMUT changed to a Corporate, it always maintained its debenture and it did not undergo the registration process of changing its name in its debenture. According to PT Bank SUMUT, the reason why it has debenture is based on the Decree of the Minister of Internal Affairs No. SK.61/DJA/1979 on the Appointment of Bank Pembangunan Daerah as a legal entity and because all its shares are owned by the government and all its assets did not change, while the obligation of Bank SUMUT on its assets is regulated in its statutes which are convened in the General Shareholders’ Meeting if there is any change.. Keywords: Certificate, Ownership, Legal Entity, Company